2018
DOI: 10.1002/chem.201804315
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐Responsive Properties of Aggregation‐Induced‐Emission Compounds Containing a 9,10‐Distyrylanthracene Moiety

Abstract: Two 9,10-distyrylanthracene-based luminophores exhibiting aggregation-induced emission and stimuli-responsive properties were synthesized. Seven- or five-color luminescence switching based on a single organic molecule was achieved for the first time. These phase transitions can be induced by physical stimuli such as grinding by mortar and pestle, heating, and exposure to the vapors of organic solvents. Moreover, a strategy for the design of new mechanoresponsive materials with π-conjugated luminophores is prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 36 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…[34,178] Temperature is one of the external forces to drive the transformation of aggregate structures and other factors such as pH, pressure and solvent could also influence the dynamics of aggregates. [179][180][181][182] Recently, Gong et al reported a dynamically Figure 8. A) Fluorescent protein chromophore 4-hydroxybenzylideneimidazolinone (HBI) can be modulated to serve as a fluorogenic probe to detect protein aggregates.…”
Section: Dynamic Aggregatesmentioning
confidence: 99%
“…[34,178] Temperature is one of the external forces to drive the transformation of aggregate structures and other factors such as pH, pressure and solvent could also influence the dynamics of aggregates. [179][180][181][182] Recently, Gong et al reported a dynamically Figure 8. A) Fluorescent protein chromophore 4-hydroxybenzylideneimidazolinone (HBI) can be modulated to serve as a fluorogenic probe to detect protein aggregates.…”
Section: Dynamic Aggregatesmentioning
confidence: 99%
“…[6,[20][21][22] The term piezofluorochromica ggregation-induced emission (PAIE) was even introduced. [23] Many pure organic mechanochromic materials with AIE-activem olecules were thus reported, [24][25][26][27][28][29][30][31] along with organoboron complexes. [32,33] Regarding metal-based compounds that combine AIE and mechanochromic properties, few studies have been reported, with examplesb ased on iridium(III), [34][35][36][37][38][39] cadmium(II), [40] zinc(II), [41,42] and gold(I) [43] complexes.…”
Section: Introductionmentioning
confidence: 99%
“…2.66 Å, Figure ) and CH/π interactions (ca. 2.99 Å, Figure S14, Supporting Information) to form a molecular layer . Between two molecular layers, each CJ-01 molecule has CH/π interactions with surrounding molecules (ca.…”
Section: Resultsmentioning
confidence: 99%